Egg yolk antibodies and nanotechnology applied to animal health and production - Bellingeri, Romina Valeria (2018)
Nanotechnology is a rapidly developing area of science and technology, which deals with the application, production and processing of materials with sizes less than 100nm (a nanometer being one billionth of a meter). In addition, it is an interdisciplinary science comprising of various disciplines such as physics, chemistry, electronics, material science, health science, biology, and veterinaryscience, and it has impact on many industries